Pola Komunikasi Efektif dalam Pencegahan Perilaku Bullying Ditinjau dari Prophetic Parenting - Risma Salsa Billah; Nazwa Zahra; Indy Auliya; Yuni Anggraeni; Hendar Riyadi; Esty Faatinisa; Silmy Halwany (Lembaga Pengembangan Kinerja Dosen, 2025)
The Importance of Family Communication in Bullying Prevention Bullying is a global social issue with negative impacts, even extending into elementary school environments. Data indicates that bullying cases, including physical, mental, and cyber violence, remain high in Indonesia. The effects of bullying are not limited to the victims but also extend to the perpetrators, who may experience deviant behavior, psychological disorders, and even suicidal ideation. There are three main contributing factors to bullying: internal factors (such as violence at home), external factors (peer groups, school, play environments), and situational factors. The family, as the smallest institution, plays a significant role in shaping a child's social interactions and character. Poor communication within the family can contribute to bullying behavior. Conversely, effective communication can prevent bullying, especially when implemented within a prophetic parenting style that emulates the educational methods of the Prophet.